India's response to the Chinese Belt and Road Initiative: new partners and new formats - Wagner, Christian; Tripathi, Siddharth (2018)
Abstract: India has been exploring the response to China’s growing influence and its Belt and Road Initiative (BRI) for long. The contours to find viable alternatives to this challenge are now becoming visible. India is slowly transitioning to increased - and previously unthinkable - cooperation with other states in South Asia. Within its extended neighbourhood, India has developed new formats of cooperation with Japan, the USA and Australia that are directly or indirectly positioned against China. For Germany and Europe, this shift in Indian foreign policy opens new avenues for cooperation. (author's abstract)